Treating Posttraumatic Stress Disorder: A Timely Update on Therapeutic Strategies - Tucker, Lorelei; Li, Yong; Zhang, Quanguang (Journal of Psychology and Psychotherapy Research, 2020)
Posttraumatic stress disorder (PTSD) is a psychological disorder that can develop after an individual experiences or witnesses a traumatic event. PTSD is startlingly common in veterans, victims of assault, those undergoing extreme medical care, and the clinicians that treat them. This growing mental health crisis has been dramatically exacerbated by the stressors and tragic events of the ongoing global COVID-19 pandemic. In this review, we will discuss the different classes of treatment for PTSD and examine current lines of research in each. First, we explore how the field of psychotherapy approaches PTSD, with focus placed on exposure therapy, cognitive behavioral therapy, and more. We then describe current pharmacological strategies for PTSD treatment and several prominent therapeutic strategies currently undergoing clinical and pre-clinical trials. Next, we investigate novel approaches that integrate principles of psychotherapy with seemingly unconventional elements and discuss how these unique components may impact recovery. Finally, we explore how telemedicine has been implemented to expand access to care, which is particularly critical in a time of social distancing and economic disparity. We hope that by summarizing current clinical practice and outlining cutting-edge research, this review can elucidate the field and highlight gaps in knowledge that merit further investigation that may lead to more effective and accessible treatment for PTSD patients.